Analisis Kepuasan Masyarakat Terhadap Kualitas Pelayanan Pada Pengadilan Negeri Simalungun Menggunakan Metode Algoritma C4.5 - Rahayu, Sri; Damanik, Irfan Sudahri; Fauzan, M (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2021)
This study aims to analyze the level of community satisfaction with services in the District Court Simalungun using the C4.5 Algorithm method. The data source used in this study was taken with an instrument in the form of a questionnaire with closed and open answers, where the data is in the form of numbers and analyzed static descriptive. The study population was all service users in the District Court Simalungun, including Procedures, Service Time, Costs/ Tariffs, Implementing Behavior, etc. After doing the calculations manually, the verification is also done using the application, namely RapidMiner. From the analysis process, it can be seen that the responsive aspect is the most dominant aspect in determining the level of community satisfaction at the District Court Simalungun